Lead knee extension contributes to drag-flick performance in field hockey - Ladru, B. J.; Langhout, R.; Veeger, D. J.; Gijssel, M.; Tak, I. (International Journal of Performance Analysis in Sport, 2019)
Understanding the biomechanics of the drag-flick is important for refining the performance of this task in field hockey. The aim of this study was to determine whether the maximal knee angle and maximal angular velocity of the lead knee extension are associated with ball speed in elite drag-flick players. The kinematics of the drag flick was studied in 19 elite field-hockey players who performed 15 drag-flick shots each towards a target located 1.30 m high at optimal speed. A motion capture suit was used to capture full body drag-flick behaviour sampling at 240 Hz. Multiple regression analyses were used to study the association between both the maximal knee flexion angle and maximal angular velocity of the leading knee extension and ball speed. Significant positive associations were found between knee extension velocity and ball speed (R2 = .127, p < .001). A higher knee extension velocity resulted in higher ball speeds within the individual, without negatively affecting the accuracy. It is advised to train, within an elite drag-flick group, for higher knee extension speed to improve the drag-flick performance. Whether training to improve this parameter results in higher ball speeds should be subject of future studies.